2021
DOI: 10.21273/hortsci15983-21
|View full text |Cite
|
Sign up to set email alerts
|

Yield and Quality of Carrot Cultivars with Eight Nitrogen Rates and Best Management Practices

Abstract: Carrot (Daucus carota) production has increased in North Florida and South Georgia since 2015. Deep sandy soils, moderate winter climate, availability of irrigation water, and proximity to eastern markets are favorable for carrot production in the region. Nitrogen (N) is required for successful carrot production, and the current recommended N application rate in Florida is 196 kg·ha−1. The objective of this study was to verify the recommended N rate for the sandy soils of North Florida using current industry s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
(17 reference statements)
0
1
1
Order By: Relevance
“…However, a yield plateau could not be identified over the range of included N rates. While results contrast with findings from other carrot studies under comparable climate and soils (Makries & Warncke, 2013;Noyes, 2018;Warncke, 1996), data suggest that under certain conditions (e.g., low soil cation exchange capacity, limited soil profile N supply, high-yielding varieties, and weather conducive to N loss) higher total fertilizer N rates may be required to maximize yield (Hochmuth et al, 1999(Hochmuth et al, , 2021Warncke et al, 2004;. High carbon previous crop residues (e.g., corn in this study) may also increase carrot N requirements.…”
Section: Tradeoffs In N Topdress Strategiescontrasting
confidence: 60%
“…However, a yield plateau could not be identified over the range of included N rates. While results contrast with findings from other carrot studies under comparable climate and soils (Makries & Warncke, 2013;Noyes, 2018;Warncke, 1996), data suggest that under certain conditions (e.g., low soil cation exchange capacity, limited soil profile N supply, high-yielding varieties, and weather conducive to N loss) higher total fertilizer N rates may be required to maximize yield (Hochmuth et al, 1999(Hochmuth et al, , 2021Warncke et al, 2004;. High carbon previous crop residues (e.g., corn in this study) may also increase carrot N requirements.…”
Section: Tradeoffs In N Topdress Strategiescontrasting
confidence: 60%
“…Westerveld et al (2006a) point out that the accumulation of N in foliage has priority over the root until 53 days after sowing (DAS); they also add that the total N content in the roots decrease during the cycle, while in the leaves it decreased around 80 and 100 DAS; the greatest absorption occurred between 50 and 60 DAS and the total N absorbed by the plant at the end of the cycle was 380 kg ha -1 . Hochmuth et al (2021) evaluated the application of eight nitrogen fertilization rates (56,112,168,224,280,336,392 and 448 kg ha -1 ); a regression analysis showed that the optimal dose was 206 kg ha -1 N, reaching a commercial yield of 71.3 t ha -1 . For Montazar et al (2021) the total N accumulated at harvest ranged between 205.4 kg ha -1 (almost 52% in roots) and 350.5 kg ha -1 (almost 64% in roots), although none of the rates of N application evaluated showed a significant relationship with performance.…”
mentioning
confidence: 99%